The Impact of Concomitant Meniscus Repair on Functional and Patient Reported Outcomes at Return to Activity in Paediatric Patients Undergoing ACL Reconstruction. Issue 5 (31st May 2022) - van Gennip, Stijn; Romanchuk, Nicholas; Flaxman, Teresa; Bel, Michael Del; Livock, Holly; Kontio, Ken; Benoit, Daniel L; Carsen, Sasha
Background: Paediatric patients undergoing Anterior Cruciate Ligament (ACL) reconstruction often present with a repairable meniscus tear. When a conservative early post-operative rehabilitation protocol is used to protect the meniscus repair, some have wondered whether this has an effect on functional and subjective outcomes, or time required, at return to activity. Purpose: The goal of this study was to compare the quantitative lower limb functional measures and subjective patient reported outcome scores at Return to Activity (RTA) in paediatric patients undergoing ACL reconstruction, with or without meniscus repair. Methods: This study was performed as a retrospective comparative cohort analysis of prospectively collected data in paediatric patients undergoing ACL reconstruction. Inclusion criteria for this study included a full data set and a visit to our biomechanics lab post-operatively, after being cleared for RTA by their attending surgeon. If a repairable meniscus injury was present, it was repaired concurrently with ACL reconstruction. Patients with a meniscus repair were provided rehabilitation guidelines that included partial weightbearing and limited range of motion (ROM) for six weeks, whereas full weightbearing and unrestricted ROM was recommended for the non-meniscal repair group. Postoperative quantitative knee functional outcome variables (drop vertical jump ground reaction forces, isometric knee extension/flexion strength, and hip abduction strength) were expressed as limb symmetry indices (LSIs; reconstructed limb/uninjured limb). Patient reported subjective knee outcome scores (Tegner and HSS Pedi-FABS) were also obtained. Differences in outcome measures were assessed using Mann-Whitney U-test and independent T-tests. Results: Twenty-four paediatric ACL reconstruction patients met criteria for inclusion in this study. Thirteen patients had a meniscus repair (median age 15 (13-17)) and 11 patients did not (median age 15.8 (14-17)). The median days between surgery and follow-up was 267 (168-460) days for the meniscus repair group and 251 (167-435) days for the non-meniscus repair group. There were no differences between the groups for the postoperative drop vertical jump test (p=0.21), knee extension/flexion strength (p=0.88/0.46) and hip abduction strength (p=0.46). Both groups also displayed similar Tegner (6.1/6.2) and Pedi-FABS (12.5/12.8) scores. Conclusion: Despite conservative weight-bearing and range of motion restrictions, repair of the meniscus in combination with ACL reconstruction in pediatric patients does not appear to induce a meaningful strength deficit at the return-to-activity evaluation phase, and is therefore not expected to influence return to activity in comparison with non-meniscus repair patients. This is important guidance for paediatric patients, families, and rehabilitation professionals involved in the care of young athletes. Table 1. Patient characteristics Table 2. Post-operative patient reported outcome scores